SOSIALISASI PERENCANAAN DAN PERANCANGAN MUSHOLA DI DESA MENUR KECAMATAN MRANGGEN - Mutiawati Mandaka; Adi Sasmito; Carina Sarasati; Taufiq Rizza Nuzuluddin; Abdul Hafidz Al Rasyid (LPPM-Universitas Batam, 2024)
The village office should be equipped with mushola which aims to support supportingfacilities and infrastructure for both village office officials and the local community. Theprayer room is not only used as a place of worship for Muslims, but can be used as a placefor education, regular community meetings, and other activities with the permission of themanagement. This community service activity carried out in Menur Village aims toencourage mushola in the Menur Village Office area. The method used is by conducting alocation survey and literature study as well as discussions with the Menur Village Office andthe local community to collect information and data which will then be processed to planand design the prayer room building according to needs. The result of this communityservice is mushola design that has been adapted to needs and is expected to be acceptedand realized. Apart from being a means of transferring knowledge to the community, thiscommunity service activity is also a good synergy between educational institutions, in thiscase LPPM Panadaran University and the people of Menur Village, Mranggen District, DemakRegency.